Research of the Transmission System Motion Solution Generated Technique of Helicopter Main Reducer - Tang Suiying; Wu Liyan; Yang Xiaohui; Chen Ce (Jixie chuandong)
The helicopter transmission system is taken as the research object,transmission scheme was conducted exhaustively and filtered to generate the transmission system principle solutions automatically. The transmission units are extracted based on existed helicopter transmission data,the corresponding graph models are established and transformed to mathematical language for computer processing. Based on rule-based reasoning,the helicopter transmission system principle solutions are achieved automatically by two steps,generated graph models of the transmission schemes and generated label information of the graph models. Several rules are developed to filter those schemes,the schemes are listed after filtering in the end.